Evaluasi Kinerja BPK dalam Meningkatkan Akuntabilitas dan Transparansi Keuangan Pemerintah Daerah - Miralda Salsabila Aisyah; Amanda, Adela; Fakia, Isna; Mariana Mariana (CV. Kalimasada Group, 2024)
This study aims to analyze the effectiveness of audits conducted by the Audit Board of Indonesia (BPK) in enhancing the accountability of regional financial management through the identification of deviations and implementable recommendations. The study also aims to assess the capacity and independence of BPK, including auditor competence and the utilization of technology, in maintaining the objectivity and quality of regional government financial oversight. The research methodology uses a literature review approach, analyzing, comparing, and synthesizing various relevant sources such as academic journals, books, and other documents. The literature review is a method placed at the top of the hierarchy of evidence, providing a strong theoretical foundation and high reliability in understanding a particular issue. The findings of this study indicate that BPK plays an important role in promoting transparency and accountability in regional financial management. The effectiveness of the audit is reflected in the quality of findings and recommendations, although it is often hindered by the low implementation of recommendations by regional governments. Additionally, auditor capacity, the use of modern technology, and BPK's independence are key factors influencing the success of oversight. Challenges such as political intervention and resource limitations need more attention to improve BPK's performance.